Safety and efficacy of rabies immunoglobulin in pediatric patients with suspected exposure. Issue 7 (3rd July 2021) - Hobart-Porter, Nicholas; Stein, Michal; Toh, Naveh; Amega, Novinyo; Nguyen, Huy-Binh; Linakis, James
ABSTRACT: Rabies is a deadly viral zoonosis with global disease burden. Following exposure to a rabid animal, post-exposure prophylaxis (PEP) is the standard of care for unvaccinated persons. Despite the large proportion of pediatric cases, limited safety and efficacy data exist for use in pediatric patients. We report the safety, efficacy, and immunogenicity of a phase 4, prospective, 2-center, open-label, single-arm clinical trial evaluating human rabies immunoglobulin (HRIG150; KEDRAB 150 IU/mL) as part of PEP in patients (aged <17) with suspected or confirmed rabies exposure, where PEP was indicated. Thirty participants received 20 IU/kg HRIG150 infiltrated into the detectable wound site(s), with any remainder injected intramuscularly, concomitantly with the first of a 4-dose series (days 0, 3, 7, and 14) of rabies vaccine. Rabies virus neutralizing antibody (RVNA) titers and tolerability were assessed on day 14 following administration. Participant safety was monitored for 84 days. No serious adverse events, rabies infections, or deaths were recorded. Twenty-one participants (70.0%) experienced a total of 57 treatment-emergent adverse events (TEAEs) within 14 days following administration. Twelve participants (40.0%) experienced a total of 13 adverse events deemed treatment related. All TEAEs were mild in severity. On day 14, 28 participants (93.3%) had RVNA levels of ≥0.5 IU/mL (mean±standard deviation: 18.89 ± 31.61). These results demonstrate that HRIG150 is well tolerated and effective in pediatric patients as a component of PEP. To the authors' knowledge, this study is the first to establish pediatric safety and efficacy of HRIG in the US.